Integrated analysis of randomized controlled trials evaluating bortezomib + lenalidomide + dexamethasone or bortezomib + thalidomide + dexamethasone induction in transplant-eligible newly diagnosed multiple myeloma - Rosiñol, Laura; Hebraud, Benjamin; Oriol, Albert; Colin, Anne-Laurène; Ríos Tamayo, Rafael; Hulin, Cyrille; Blanchard, María Jesús; Caillot, Denis; Sureda, Anna; Hernández, Miguel Teodoro; Arnulf, Bertrand; Mateos, Maria-Victoria; et al. (Frontiers in Oncology, 2023)
Objective Providing the most efficacious frontline treatment for newly diagnosed multiple myeloma (NDMM) is critical for patient outcomes. No direct comparisons have been made between bortezomib + lenalidomide + dexamethasone (VRD) and bortezomib + thalidomide + dexamethasone (VTD) induction regimens in transplant-eligible NDMM. Methods An integrated analysis was performed using patient data from four trials meeting prespecified eligibility criteria: two using VRD (PETHEMA GEM2012 and IFM 2009) and two using VTD (PETHEMA GEM2005 and IFM 2013-04). Results The primary endpoint was met, with VRD demonstrating a noninferior rate of at least very good partial response (≥ VGPR) after induction vs VTD. GEM comparison demonstrated improvement in the ≥ VGPR rate after induction for VRD vs VTD (66.3% vs 51.2%; P = .00281) that increased after transplant (74.4% vs 53.5%). Undetectable minimal residual disease rates post induction (46.7% vs 34.9%) and post transplant (62.4% vs 47.3%) support the benefit of VRD vs VTD. Treatment-emergent adverse events leading to study and/or treatment discontinuation were less frequent with VRD (3%, GEM2012; 6%, IFM 2009) vs VTD (11%, IFM 2013-04). Conclusion These results supported the benefit of VRD over VTD for induction in transplant-eligible patients with NDMM. The trials included are registered with ClinicalTrials.gov (NCT01916252, NCT01191060, NCT00461747, and NCT01971658).